EKSPRESI WAJAH DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Ari Syarizal, Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2019)
The creation of this final work aims to visualize the crisisabout ignorance of human facial expression, The method and process of work are visualized through works of art several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the Concept, (5) Completion. The results of the visualization of face expression in contemporary realized works of art in this graphic work are 10 works with the title : (1) bukan hidung belang, (2) terbatas 1, (3) keras kepala, (4) dua sisi, (5)UGD ( urang gawat darurat ),(6) sombong,(7)emosi luar batas,(8)pembunuh karakter,(9) topeng, (10)terbatas 2.Keywords: expressions, exploration, visual.